2019
DOI: 10.5114/pjr.2019.91375
|View full text |Cite
|
Sign up to set email alerts
|

T1 and T2 mapping of articular cartilage and menisci in early osteoarthritis of the knee using 3-Tesla magnetic resonance imaging

Abstract: Purpose: 3-Tesla magnetic resonance imaging (MRI) T1 and T2 mapping to detect and quantify cartilage matrix and meniscal degeneration between normal healthy volunteers and early osteoarthritis patients. Material and methods:A prospective study including 25 patients and 10 healthy volunteers was done. Patients with symptoms of early osteoarthritis and Kellgren-Lawrence grade I-II on plain radiograph were included for MRI knee. Patients with inflammatory arthritis, infection, trauma, and history of knee surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 33 publications
6
34
1
Order By: Relevance
“…In agree with Mittal et al (2019) (22), that reported lack of difference in average articular cartilage thickness between OA patients and controls, with p value > 0.05, our study results showed that there was a non-significant difference between cartilage thickness in OA patients and controls (p = 0.16), in Contrary to the cross-sectional CT arthrography retrospective study by Omoumi et al (2015) (23) which carried on 535 consecutive knees showing that cartilage of posterior aspect of medial condyle was statistically thicker in OA knees compared to non-OA Knees (p<0.001).Also, Li et al (2007) (24) , reported that there was no significant difference in the average cartilage thickness in OA patients and control subjects (P = 0.37), and suggested that there is nosignificant correlation was found between T2 values and cartilage thickness (P > 0.05), similar to our study results that observed a non-significant negative correlation (r = -0.3) between T2 values and cartilage thickness (p > 0.05).…”
Section: Dunn Et Al (2004)supporting
confidence: 91%
“…In agree with Mittal et al (2019) (22), that reported lack of difference in average articular cartilage thickness between OA patients and controls, with p value > 0.05, our study results showed that there was a non-significant difference between cartilage thickness in OA patients and controls (p = 0.16), in Contrary to the cross-sectional CT arthrography retrospective study by Omoumi et al (2015) (23) which carried on 535 consecutive knees showing that cartilage of posterior aspect of medial condyle was statistically thicker in OA knees compared to non-OA Knees (p<0.001).Also, Li et al (2007) (24) , reported that there was no significant difference in the average cartilage thickness in OA patients and control subjects (P = 0.37), and suggested that there is nosignificant correlation was found between T2 values and cartilage thickness (P > 0.05), similar to our study results that observed a non-significant negative correlation (r = -0.3) between T2 values and cartilage thickness (p > 0.05).…”
Section: Dunn Et Al (2004)supporting
confidence: 91%
“…Therefore, researchers have reported that magnetic resonance imaging (MRI) and arthroscopy are useful in detecting the full spectrum of pathological changes within the joint tissue 5 . Although our current understanding suggests that MRI can be used to detect early KOA 7 , 8 , this method has been excluded from the diagnostic criteria for early KOA, as it is costly and cannot be frequently used 9 , 10 . Therefore, in the present study, we focused on the efficiency of ultrasonography in identifying patients with early KOA, as the technique is simple and widely available in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the present study, we focused on the efficiency of ultrasonography in identifying patients with early KOA, as the technique is simple and widely available in clinical settings. Because previous studies have already reported the usefulness of ultrasonography for meniscal evaluation, our novel dynamic ultrasonographic evaluation focused on the medial meniscus, where medial KOA findings are known to appear early 8 , 11 , 12 . Indeed, dynamic evaluation represents the strongest point of ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…T1 mapping imaging technology reflects the slow frequency interaction between water and extracellular matrix molecules in tissue, is sensitive to changes of proteoglycan content in tissue, and is independent from the signal intensity of reference tissue. In the past, it was used to quantify the degree of myocardial edema and fibrosis [14], because the tissue T1 value was relatively independent, not affected by the direction of collagen arrangement, and was also used for articular cartilage MR Relaxometry technology [15]. At present, there is little discussion on this at home and abroad.…”
Section: Mr Relaxometry Technology and Clinical Applicationmentioning
confidence: 99%